Perempuan dan Dakwah di Dataran Tinggi Gayo - Fachrur Rizha; Ali Mustafa (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
This study aims to look further at the space and role of women in dakwah development in Gayo highlands. This research use descriptive qualitative approach. To collect its data, the research use interviews and observation technique. Informants are determined based on purposive sampling. There are five informants used as the primary data source in this study: an informant represent a traditional figure, other represent a religious figure, and three represent female preacher. The study found that the dakwah conducted by women in Gayo highlands consisted of: religious lecture, counseling, learning of Al-Qur‟an reading, and economic empowerment. The dakwah conducted by women in Gayo only focused on women. Little of women preacher can preach publicly in front of men and women. This is due to the strict culture and customs in Gayo. The number of female preachers in Gayo highlands is still very small and there is a need for a regeneration program for women in the future.